Smart parking for smart cities: a novel approach to reducing frivolous parking zone determination - Atiqur Rahman; Ali Md Liton (International Journal of Informatics and Communication Technology (IJ-ICT), 2023)
Internet of things (IoT) infrastructures are rapidly expanding, which will lead to an unanticipated rise in demand for smart cities. The concept of a "smart city" has recently gained traction in urban planning circles. An IoT-based smart parking system is the focus of this article, and it allows a motorist to locate a car park and an available parking space in an indoor metropolis, all from the comfort of their own vehicle. Additional efforts are made to reduce the time spent defining parking zones. Reduced fuel use helps to cut down on pollution, as well as avoid needless travel through congested parking lots, which can help to reduce unlawful parking and alleviate traffic congestion in the city we all live in. These innovations include automobile particular identification via radio frequency identification (RFID) tags, unoccupied slot detection through the use of ultrasonic sensors, and cost calculating based largely on parking duration. The technology we've used is unique in that it runs on separate parts of the system for the hardware and the software.